Ontology-based semantic approach for construction-oriented quantity take-off from BIM models in the light-frame building industry. Issue 2 (April 2016) - Liu, Hexu; Lu, Ming; Al-Hussein, Mohamed
Highlights: Proposing ontology-based semantic framework for quantity takeoff (QTO). Establishing construction-oriented product ontology for light-frame building projects. Querying a BIM design model for construction-oriented QTO using richer vocabulary. Prototyping Autodesk Revit add-on tool with light-frame building application case. Abstract: In building information modeling (BIM), the model is a digital representation of physical and functional characteristics of a facility and contains enriched product information pertaining to the facility. This information is generally embedded into the BIM model as properties for parametric building objects, and is exchangeable among project stakeholders and BIM design programs – a key feature of BIM for enhancing communication and work efficiency. However, BIM itself is a purpose-built, product-centric information database and lacks domain semantics such that extracting construction-oriented quantity take-off information for the purpose of construction workface planning still remains a challenge. Moreover, some information crucial to construction practitioners, such as the topological relationships among building objects, remains implicit in the BIM design model. This restricts information extraction from the BIM model for downstream analyses in construction. To address identified limitations, this study proposes an ontology-based semantic approach to extracting construction-oriented quantity take-off information from a BIM design model. This approach allows users to semantically query the BIM design model using a domain vocabulary, capitalizing on building product ontology formalized from construction perspectives. As such, quantity take-off information relevant to construction practitioners can be readily extracted and visualized in 3D in order to serve application needs in the construction field. A prototype application is implemented in Autodesk Revit to demonstrate the effectiveness of the proposed new approach in the domain of light-frame building construction.